Environmental and social determinants of cardiovascular risk in women with type 2 diabetes: a life-course perspective - Cocchi, Camilla; Selleri, Valentina; Zanini, Giada; Moscucci, Federica; Sciomer, Susanna; Gallina, Sabina; Nasi, Milena; Desideri, Giovambattista; Pinti, Marcello; Borghi, Claudio; Mattioli, Anna Vittoria (Frontiers in Endocrinology, 2025)
BackgroundCardiovascular disease (CVD) remains the leading cause of morbidity and mortality among women with type 2 diabetes (T2DM). The interplay between sex-specific biological factors, social determinants, and environmental exposures amplifies cardiometabolic risk across the female life course.ObjectivesThis manuscript explores how socioeconomic disparities, environmental pollution, chronic stress, food insecurity, and climate change synergistically increase the burden of T2DM and cardiovascular complications in women, and reviews potential preventive interventions including dietary strategies.MethodsA comprehensive narrative review was conducted, synthesizing current evidence on the exposome, social inequities, environmental insults, and evidence-based lifestyle interventions that contribute to or mitigate the development and progression of T2DM and CVD in women.ResultsLower socioeconomic status, limited education, housing instability, and inadequate access to healthcare and nutritious foods profoundly affect T2DM management and CVD prevention in women. Concurrently, exposure to air pollutants (PM2.5, NO2, O3), climate change-induced food insecurity, and heat-related stress further exacerbate insulin resistance, systemic inflammation, and vascular dysfunction. Life transitions such as gestational diabetes mellitus and menopause further magnify these risks. Current healthcare models insufficiently address these multilayered factors.ConclusionEffective cardiovascular prevention in women with T2DM requires a life-course approach that integrates biological transitions with environmental and social determinants to deliver sex-sensitive, stage-specific strategies.